Vitamin D Status and Fracture Neck of Femur among Post-Menopausal Women in Gaza Strip: A Hospital Based Study - Al-Hissi, J.H; Al-Ghaffari, M.M; Taleb, M H; Ahmed, A; Najm, AA (Arab Journal for Sciences and Research Publishing, 2016)
To determine the relationship between vitamin D status and FNOF among postmenopausal women in the Gaza Strip. Methods: A case-control study was consisted of 90 participants (45 cases and 45 controls), the study was conducted in the main governmental hospitals in Gaza Strip. Food Frequency Questionnaire (FFQ) was used to assess dietary intake of vitamin D. Anthropometric measurements were done included weight, height, and body mass index was calculated. Serum levels of phosphorus, calcium and Vitamin D were measured in both cases and controls. Results: the study revealed the following results; the percentage of both vitamin D deficiency and insufficiency levels were higher among cases with FNOF (66.4%) than among controls (26.6%) with significance statistical differences (P = 0.001). The mean of servings consumed per day from total diet vitamin D was less among cases with FNOF (1.46 ± 0.91) than controls (2.71 ± 0.94). Cases were less likely to be exposed to sunlight (53.3%) than controls (80%) (P = 0.007), on the other hand cases were also less active (2.2%) than control (53.3 %) (P = 0.00). Conclusion: Postmenopausal women with FNOF in the Gaza Strip have low serum vitamin D level and low intake of vitamin D.